Generic models for predicting pedestrian-level wind around isolated square-section high-rise buildings. Issue 220 (January 2022) - Yang, Qingshan; Xu, Xiaoda; Lin, Qiang; Tamura, Yukio
Abstract: High-rise buildings have significant effects on pedestrian-level wind in their vicinity, and are closely related to people's daily lives. The social implications of this problem have caused worldwide concern. Thus, an accurate and fast way for assessing the pedestrian-level wind environment has become increasingly important in the preliminary design of tall buildings. Some mathematical formulae for predicting pedestrian-level wind, referred to as generic models (GM), have been developed from experimental results. In this study, GMs reflecting the different contributions of physical causes, such as Type I (Slenderness) Effect and Type II (Height) Effect, on pedestrian-level wind are proposed and verified based on quantitative analyses and wind tunnel test results. The proposed GMs may be applied to assess pedestrian-level winds for various square-section high-rise and super-high-rise buildings, with widths from 25 m to 75 m, and heights from 60 m to 600 m. Highlights: Generic models for predicting speed-up effects around high-rise buildings at the early stage of building design are proposed. Proposed generic models are suitable for isolated square-sectioned buildings with aspect ratios from 2 to 15 in BLF (α = 0.27). Proposed generic models can reflect the different contributions of physical causes on pedestrian-level wind.